ON $SLDNF$-RESOLUTION IN LOGIC PROGRAMMING WITH NEGATION - Sargsyan, L.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
The paper is devoted to the logic programming with negation and with built-in predicates. General logic programs (logic programs with negation) and general goals (goals with negation) are considered. Modification of SLDNF-resolution for built-in predicates is introduced. The soundness of modified SLDNF-resolution is proved. SLDNF-resolution used in real systems (practical SLDNF-resolution) is considered and the soundness of practical SLDNF-resolution is proved.
Keywords: logic programming; negation; built-in predicates; $SLDNF$-resolution; soundness; practical $SLDNF$-resolution